2018
DOI: 10.3233/jad-170764
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Distribution and Diversity of Gut Microbial NADH:Ubiquinone Oxidoreductase Sequence Associated with Alzheimer’s Disease

Abstract: Earlier we reported induction of neurotoxicity and neurodegeneration by tryptophan metabolites that link the metabolic alterations to Alzheimer's disease (AD). Tryptophan is a product of Shikimate pathway (SP). Human cells lack SP, which is found in human gut bacteria exclusively using SP to produce aromatic amino acids (AAA). This study is a first attempt toward gene-targeted analysis of human gut microbiota in AD fecal samples. The oligonucleotide primers newly-designed for this work target SP-AAA in environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 50 publications
0
28
0
1
Order By: Relevance
“…specific of patients with AD 63. These sequences encoded for NADH:ubiquinone oxidoreductase, an enzyme involved in aromatic amino acid production 63.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…specific of patients with AD 63. These sequences encoded for NADH:ubiquinone oxidoreductase, an enzyme involved in aromatic amino acid production 63.…”
Section: Resultsmentioning
confidence: 99%
“…specific of patients with AD 63. These sequences encoded for NADH:ubiquinone oxidoreductase, an enzyme involved in aromatic amino acid production 63. High levels of these amino acids in the brain may induce cell death and neurodegeneration, and thus, the gut microbiota functionality may directly influence the AD physiopathology through this pathway.…”
Section: Resultsmentioning
confidence: 99%
“…60) According to the 16S rRNA microbial profile, the gut microbiome diversity is significantly lower in people with Clostridium clustering. 60,61) Cyanobacteria within the gut microbiota can synthesize neurotoxins such as saxitoxin and alpha-anatoxin. 62) Moreover, Citrobacter, Escherichia coli, Klebsiella, Mycobacteria, Pseudomonas, Streptococcus, Streptomyces, Staphylococcus, Salmonella, and Bacillus spp.…”
Section: Gut-muscle Axis Gut Microbiome and Physical Frailtymentioning
confidence: 99%
“…Tryptamine is increased under sporulating conditions in wheat pathogenic fungus Stagonospora nodorum [ 17 ]. The gut microbiome is altered in AD patients [ 18 , 19 ]. The gut microbiome of AD participants has decreased microbial diversity and is compositionally distinct from control age- and sex-matched individuals [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome of AD participants has decreased microbial diversity and is compositionally distinct from control age- and sex-matched individuals [ 19 ]. Our study revealed the gut bacterial sequence specific for AD patients [ 18 ]. This sequence belongs to the gene encoding Na(+)-transporting NADH: Ubiquinone reductase (NQR) while both the NQR substrate ubiquinone and Tryptophan are the products of Shikimate pathway.…”
Section: Introductionmentioning
confidence: 99%